Barrett Taxonomy Reorganization To Improve Students' Intensive Reading Ability - Muhammad Akhir; Marwiah Marwiah (Journal of Educational Science and Technology (EST), 2021)
This study aims to determine the effect of the Barrett Taxonomy Reorganization Method on the intensive reading ability of class VIII students of SMP Negeri 2 Duampanua, Pinrang Regency, 2019/2020 academic year. This type of research is a quasi-experimental design with True Experimental Design. The variables in this study were the Barrett Taxonomy Reorganization Method and intensive reading skills. The experimental group was class VIII.1 students and the control group was grade VIII.3 students of SMP Negeri 2 Duampanua, Pinrang Regency. Research data collection techniques in the form of tests. The results showed that the intensive reading ability using the Barrett Taxonomy Reorganization method was higher than the intensive reading ability using the conventional method for eighth grade students of SMP Negeri 2 Duampanua, Pinrang Regency. This is evidenced by the results of the t-test with a significance level of 5% (95% confidence level) obtained t count (3.061)> t table (0.278). The value of t count> t table shows that the intensive reading skills of the two groups differ significantly. Therefore, it can be concluded that the effect of the Barrett Taxonomy Reorganization method can not only improve students' understanding but also their reading ability.